Relayout Gudang E-Bike dengan Metode Class Based Storage untuk Mengurangi Waktu Pengambilan dan Pencarian Barang - Kharisma, Yuyun; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. HTI is an e-bike distributor that experiences constraints in warehouse layout efficiency, such as irregular placement of goods and long search times. This study aims to design a space arrangement strategy based on the frequency of goods movement, as well as to improve the warehouse layout. The Class-Based Storage method is used in product grouping. The results of the study show that redesigning the warehouse layout improves the efficiency of space use based on demand levels (classifications A, B, C). Significant changes are seen on the 1st floor of the main warehouse, which was previously dominated by classes B and C, now allocated for class A goods. The implementation of this strategy has been shown to speed up the goods retrieval process and improve overall operational efficiency.